Effect of Aloe vera coatings on fruit quality and storability of strawberry (Fragaria x ananassa) - SINGH, D B; SINGH, RAJBIR; KINGSLY, A R P; SHARMA, R R (The Indian Journal of Agricultural Sciences, 2011)
Plant-based edible coatings provide an alternative to wax coating or chemical treatments for extending the postharvest life of fresh fruits and vegetables. The effect of different concentrations of Aloe vera gel coatings on refrigerated strawberry quality and shelf-life was studied with the aim to extend the shelf-life of strawberries without hampering the sensory attributes. Under cold storage uncoated fruits showed increase in weight loss, colour changes, loss of firmness and quality deterioration during the storage (16 days). However strawberries treated with Aloe vera gel (1: 3 ratio) significantly reduced weight loss (9.99±2.1% compared to 13.79±0.13% in control), maintained colour, firmness, quality characteristics (TSS of 8.4° Brix compared to 7.0 ° Brix in control, acidity of 1.37% compared to 0.83% in control and ascorbic acid of 45±0.4 mg/100 g compared to 30±0.5 mg/100 g in control) and ultimately extended storability up to 16 days when stored at 5°C and RH 95%. The sensory analysis for taste, aroma and flavours further confirmed the findings. Aloe vera has medicinal and antioxidant properties; therefore use of such plant-based alternative to post-harvest chemical treatments could not only have large acceptance among consumers but could also find commercial application.